Systemic and Local Cytokine Profile following Spinal Cord Injury in Rats: A Multiplex Analysis - Mukhamedshina, Yana O.; Akhmetzyanova, Elvira R.; Martynova, Ekaterina V.; Khaiboullina, Svetlana F.; Galieva, Luisa R.; Rizvanov, Albert A. (Frontiers in Neurology, 2017)
Changes of the cytokine profile in blood serum and in the area of traumatic spinal cord injury (SCI) in rats were dealt with in this article. Our study has shown that an inflammatory reaction and immunological response are not limited within the CNS after SCI, but widespread. This fact was confirmed by changes detected in a cytokine profile in blood serum samples (MIP-1α, IL-1α, IL 2, IL-5, IL-1β, MCP-1, RANTES). There were also changes in the levels of MIP-1α, IL-1α, IL-2, IL-5, IL-18, GM-CSF, IL-17α, IFN-γ, IL-10, IL 13, MCP-1, GRO KC CINC-1 in samples of the rat injured spinal cord. The results underscore the complex cytokine network imbalance exhibited by SCI and show significant changes in concentrations of 14 cytokines/chemokines with different inflammatory and immunological activities.